Multicenter, Prospective Validation of a Phenotypic Algorithm to Guide Carbapenemase Testing in Carbapenem-Resistant Pseudomonas aeruginosa Using the ERACE-PA Global Surveillance Program. (13th December 2021) - Gill, Christian M; Aktaþ, Elif; Alfouzan, Wadha; Bourassa, Lori; Brink, Adrian; Burnham, Carey-Ann D; Canton, Rafael; Carmeli, Yehuda; Falcone, Marco; Kiffer, Carlos; Marchese, Anna; Martinez, Octavio; et al.
Abstract: Background: Carbapenemase-producing, carbapenem-resistant Pseudomonas aeruginosa (CP-CRPA) is a global challenge. However, detection efforts can be laborious because numerous mechanisms produce carbapenem resistance. A minimum inhibitory concentration–based algorithm (imipenem- or meropenem-resistant plus ceftazidime-nonsusceptible plus cefepime-nonsusceptible) was proposed to identify the isolates most likely to harbor a carbapenemase; however, prospective validation in geographies displaying genotypic diversity and varied carbapenemase prevalence is warranted. Methods: CRPA isolates were collected during the Enhancing Rational Antimicrobials for P. aeruginosa (ERACE-PA) global surveillance program from 17 sites in 12 countries. Isolates underwent susceptibility testing following local standards to ceftazidime, cefepime, and ceftolozane/tazobactam. Isolates underwent initial phenotypic carbapenemase screening followed by molecular testing if positive. The primary algorithm criteria were applied, and results were compared with phenotypic carbapenemase results to assess the performance of the algorithm. A secondary criterion, the algorithm criterion or imipenem- or meropenem-resistant plus ceftolozane/tazobactam-nonsusceptible, was assessed. Results: A total of 807 CRPA were assessed, and 464 isolates met the algorithm criteria described above. Overall, testing was reduced by 43% compared with testing all CRPA. Carbapenemase-positive isolates missed by the algorithm were largely driven by Guiana extended spectrum (GES). Addition of the criterion of imipenem- or meropenem-resistant plus ceftolozane/tazobactam-nonsusceptible decreased the number of CP-CRPA missed by the algorithm (21 vs 40 isolates, respectively), reducing number of isolates tested by 39%. Conclusions: Application of the initial algorithm (imipenem- or meropenem-resistant plus ceftazidime-nonsusceptible plus cefepime-nonsusceptible) performed well in a global cohort, with 33% phenotypically carbapenemase-positive isolates. The addition of imipenem- or meropenem-resistant plus ceftolozane/tazobactam-nonsusceptible reduced the number of phenotypically carbapenemase-positive isolates missed and may be useful in areas with a prominence of GES.